1996
DOI: 10.1029/96gl00086
|View full text |Cite
|
Sign up to set email alerts
|

Deduction of temperature profile from MST radar observations of vertical wind

Abstract: From the temporal spectra of vertical wind obtained from MST radar observations, the Brunt‐Vaisala frequency is identified. Altitude profile of temperature in troposphere and lower stratosphere is derived from the altitude profile of the Brunt‐Vaisala frequency thus obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 5 publications
1
49
0
Order By: Relevance
“…These observations were carried out as part of the equatorial wave studies campaign (Sasi et al, 2003). The temperatures in the 3 to 22 km altitude range are derived from the vertical wind data of ∼2-h duration (from 20:00 IST-22:00 IST) following the method derived by Revathy et al (1996). The standard error of these measurements is 0.7 K at 7 km and 1.6 K at 20 km (Revathy et al, 1998).…”
Section: Datamentioning
confidence: 99%
“…These observations were carried out as part of the equatorial wave studies campaign (Sasi et al, 2003). The temperatures in the 3 to 22 km altitude range are derived from the vertical wind data of ∼2-h duration (from 20:00 IST-22:00 IST) following the method derived by Revathy et al (1996). The standard error of these measurements is 0.7 K at 7 km and 1.6 K at 20 km (Revathy et al, 1998).…”
Section: Datamentioning
confidence: 99%
“…As has already been attested (Ecklund et al, 1985;Röttger, 1985;Revathy et al, 1996), the spectral representation of these variations generally show a peak corresponding to B-V and enable an easy detection of this parameter.…”
Section: Introductionmentioning
confidence: 81%
“…9). From then, T profiles can be deduced as has already be demonstrated by Revathy et al (1996) and Mohan et al (2001).…”
Section: Temperature Retrieval With the Vertical Wind Variation Technmentioning
confidence: 99%
“…The BruntVäisälä frequency can be characterized by a spectral peak at the Brunt-Väisälä frequency with a steep decrease on its high frequency side and a shallow decrease on the low frequency side (Rastogi, 1975;Röttger, 1980aRöttger, , 1980bEcklund et al, 1985). Making use of Röttger's (1984) method, Revathy et al (1996) had derived temperature from the observed radar vertical velocities by identifying the Brunt-Väisälä frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…First, vertical velocities are collected continuously using the radar and are subjected to Fast Fourier Transform (FFT) analysis to obtain Brunt-Väisälä oscillations. From the measured BruntVäisälä oscillations, temperature profile is obtained from the radar observations following Revathy et al (1996). The various terms required for the retrieval of vertical profiles of humidity are the eddy dissipation rate, ε, the volume reflectivity, η, and the potential refractive index gradient, M .…”
mentioning
confidence: 99%